Efficiency above 12% for 1 cm2 Flexible Organic Solar Cells with Ag/Cu Grid Transparent Conducting Electrode. Issue 22 (30th September 2019) - Han, Yunfei; Chen, Xiaolian; Wei, Junfeng; Ji, Guoqi; Wang, Chen; Zhao, Wenchao; Lai, Junqi; Zha, Wusong; Li, Zerui; Yan, Lingpeng; Gu, Huiming; Luo, Qun; et al.
Abstract: With the rapid progress of organic solar cells (OSCs), improvement in the efficiency of large‐area flexible OSCs (>1 cm 2 ) is crucial for real applications. However, the development of the large‐area flexible OSCs severely lags behind the growth of the small‐area OSCs, with the electrical loss due to the large sheet resistance of the electrode being a main reason. Herein, a high conductive and high transparent Ag/Cu composite grid with sheet resistance <1 Ω sq −1 and an average visible light transparency of 84% is produced as the transparent conducting electrode of flexible OSCs. Based on this Ag/Cu composite grid electrode, a high efficiency of 12.26% for 1 cm 2 flexible OSCs is achieved. The performances of large‐area flexible OSCs also reach 7.79% (4 cm 2 ) and 7.35% (9 cm 2 ), respectively, which are much higher than those of the control devices with conventional flexible indium tin oxide electrodes. Surface planarization using highly conductive PEDOT:PSS and modification of the ZnO buffer layer by zirconium acetylacetonate (ZrAcac) are two necessary steps to achieve high performance. The flexible OSCs employing Ag/Cu grid have excellent mechanical bending resistance, maintaining high performance after bending at a radius of 2 mm. Abstract : High performance flexible organic solar cells with efficiency above 12% for 1 cm 2 cells are fabricated using a Ag/Cu composite grid electrode. The excellent optical and electrical properties of the Ag/Cu electrode contribute to the high performance and good mechanical resistance of the flexible organic solar cell.